Sensitivity of midgut physiological parameters of Lymantria dispar L. larvae to benzo[a]pyrene in populations with different multigeneration contact to environmental pollutants. (1st November 2021) - Grčić, Anja; Ilijin, Larisa; Matić, Dragana; Filipović, Aleksandra; Mrdaković, Marija; Todorović, Dajana; Perić-Mataruga, Vesna
Abstract: Accumulation of organic pollutants in the environment calls for sensing physiological parameters adequate to indicate the presence of contaminants and their effects on ecosystems. Evidence points to the importance of insect adaptations in their habitats for the assessment of sensitive biomarkers so we examined the influence of origin and multigenerational adaptations of the Lymantria dispar larvae to chronic benzo[ a ]pyrene (B[ a ]P) treatment under laboratory conditions. The main aim was to compare reactions of larvae from unpolluted and polluted forests using alkaline phosphatase (ALP), acid phosphatase (ACP), and carboxylesterase (CE) specific activities in the midgut, including electrophoretic isoform patterns; midgut expression levels of Hsp70, larval development time (DT), and midgut mass (MM), after chronic exposure to 5 and 50 ng of B[ a ]P/g dry food weight. The biomarker potential of these parameters regarding larval pre-exposure history to pollution was estimated by principal component analysis (PCA). B[ a ]P treatment resulted in inhibition of ALP activity, a rise of CE activity, and reduction of MM in larvae from the unpolluted forest, while the population from the polluted forest showed significant elevation of Hsp70 expression in the midgut, prolonged DT, and reduction of MM. PCA confirmed variations in responses of the selected parameters regarding population origin. The obtained results provide insight into insect population variability concerning physiological responses to pollutants. It is indicative that all investigated physiological parameters of L. dispar larvae showed origin-dependent responses to long-term presence of B[ a ]P, which may be of great importance in ecotoxicological research. Graphical abstract: Image 1 Highlights: Lymantria dispar of different pre-exposure histories were exposed to benzo[ a ]pyrene . Midgut physiological parameters of larvae are sensitive to benzo[ a ]pyrene presence. Pre-exposure history of larvae populations sets the specific response of parameters. Principal component analysis point out the population-based divergence. Different pollution biomarkers are suitable for different insect populations.